Synthesis and Properties of Low Band Gap Organic Semiconductors for Solar Cell Applications - Yücekan, İlke (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
The development of new PV technology is essential with increasing consumption of fossil fuels and seems to be the only way to cover energy demand. The primary objective should be accomplished efficiency between cost and power conversion efficiency. Moreover, the applicability of new materials is primarily determined by their balanced electrical, thermal, physical and chemical properties. In this thesis, a new series of low band gap aromatic polyimides were successfully synthesized to be used in photovoltaic applications as next generation organic semiconductor material. To this purpose, chitosan biopolymer based two aromatic polyimide functionalized with commercially available perylene and naphthalene organic semiconductors and previously synthesized high molecular weight naphthalene based polyimide have been characterized in detail by studying their , photophysical, thermal and electrochemical properties through the data obtained from NMR, FTIR, GPC, UV-vis, Fluorescence, DSC, TGA and CV and SQWV. Incorporation of the hydrophobic chromophore units within the hydrophilic polymeric backbones yielded a network-like structure and maintained good solubility. The compounds showed extraordinary thermal stabilities and high molar absorption coefficients. They possessed excimer type emission and aggregation formation which confirmed the electroactive species both in ground and excited state. The products showed outstanding electrochemical stability and also undergoes only one reversible reduction and oxidation in solid state which make them candidate as Donor/Acceptor polymer for PV technology. Keywords: Perylene, Naphthalene, Donor/Acceptor Polymer, High Molar Absorptivity

ÖZ: Fosil yakıtlarının artan tüketimi karşısında, yeni PV teknolojilerinin geliştirilmesi zaruridir ve enerji talebinin karşılanması için tek kurtuluş yolu olarak gözükmektedir. Birincil amaç, maliyet ve güç dönüşüm verimliliği arasındaki tutarlılığın gerçekleştirilmesidir. Ayrıca, elektriksel, ısı, fiziksel ve kimyasal özellikleri bakımından dengeli yeni materyallerin uygulanabirliği belirlenmelidir. Bu tezde, fotovoltaik uygulamalarda yeni nesil organik yarı-iletken malzeme olarak kullanılmak üzere düşük bant aralığına sahip aromatik poliimidlerin sentezi gerçekleştirilmiştir. Bu amaçla, ticari olarak temin edilebilen naftalin ve perilen organik yarı iletkenler ile fonksiyonlandırılmış kitozan tabanlı iki aromatik poliimid ile daha önce sentezlenmiş olan naftalin esaslı yüksek molekül ağırlıklı poliimidin fotofiziksel, termal ve elektrokimyasal özellikleri NMR, FTIR, GPC, UV-vis, Fluoresans, DSC, TGA ve voltametri ölçümleri ile karakterize edilmiştir. Sentezlenen maddeler, hidrofobik kromofor birimlerinin hidrofilik yapıdaki polimerlere dahil edilmesiyle ağ-benzeri bir yapı oluşturmuş olup iyi bir çözünürlüğe sahiptirler. Her bir polimer, yüksek molar soğurma katsayısına ve olağanüstü termal kararlılıpa sahiptir. Poliimidler eksimer tipi emisyon ve aggregasyon oluşumuna sahip olduklarından hem temelde hem de uyarılmış halde elektroaktif türlere sahiptirler. Sentezlenen ürünler, elektrokimyasal kararlılığa sahip olup, katı halde geri dönüşümlü oksidasyon ve redüksiyon potansiyeline sahiptir. Bu özellikleri sayesinde, PV teknolojisi için elektron donör/akseptör polimer olarak potansiyel birer adaydırlar. Anahtar Kelimeler: Perilen, Naftalin, Donör/Akseptör Polimer, Yüksek Molar Soğurum
Doctor of Philosophy in Chemistry. Thesis (Ph.D.)-Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 2013. 'Supervisor: Prof. Dr. Huriye İcil.
Keywords: Chemistry; Fossil Fuels - Chemistry; Green chemistry - Power Resources - Alternative & Renewable; Energy conversion; Renewable energy sources - Agricultural wastes as fuel; Perylene; Naphthalene; Donor/Acceptor Polymer; High Molar Absorptivity